(untitled) (Praxis Educativa, 2026)
This article analyzes how the role of the Program for International Student Assessment (PISA) was conceived in the government discourse of Latin American countries that took part in the assessment during the period 2012-2018. The study applied interpretive analysis techniques to two sets of official documents from the countries participating in the test. The findings highlight some convergences regarding the acceptance of PISA as an instrument for the regulation of educational systems, related to rationalist arguments that focus on the uses of the data resulting from the evaluation in two main senses: as input for the (re)design of policies, and as an indicator of the degree of progress in certain goals. However, there is also a diversity of positions regarding the purposes of participating in PISA and the uses of its results that seem to respond to factors specific to the different national contexts.